Determinants of place attachment among mineworkers: Evidence from South Africa. Issue 3 (September 2021) - Marais, Lochner; Owen, John R; Kotzѐ, Tina; Nel, Petrus; Cloete, Jan; Lenka, Molefi
Highlights: Research generally depicts place attachment in a positive light. Our study suggests attachments in mining are complex and multi-faceted. Attachments can create financial lock-ins with damaging long-term effects. Policies that induce place attachment ought to be treated with caution. Abstract: The authors argue that, given (i) the unpredictability of the mining lifecycle and (ii) global pressure to transition out of coal, researchers must take a more critical perspective on place attachment and its consequences. Research generally depicts place attachment in a positive light. The conventional understanding is that place attachment brings stability, creates assets and helps society to take on and complete long-term projects. We use evidence from case studies to question the appropriateness of this conventional wisdom and whether it should be applied blindly in the mining industry. A policy of encouraging place attachment will be counterproductive if living standards and access to quality service provision cannot be maintained. Unchecked, place attachments can create financial lock-ins that lead to long-term economic damage. The likelihood of eventual mine closure means that policies that aim to induce place attachment to encourage stability, long-range planning and asset development may not be appropriate for all mining communities. While we agree that some measure of place attachment should be encouraged through social policy throughout the mine's lifecycle, we do not agree that place attachment should be constructed as an outcome in its own right.